2005
DOI: 10.1115/1.2121747
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Planar Parallel Mechanisms While Considering Workspace, Dexterity, Stiffness and Singularity Avoidance

Abstract: It is a generally well-known fact that the design of parallel mechanisms while optimizing performance is quite difficult. In this paper, a reliable synthesis method capable of optimally selecting the geometrical parameters of planar parallel mechanisms is presented. Three different architectures are considered and a genetic algorithm is used to perform the optimization. The performance of each mechanism is evaluated according to four different criteria: workspace, singular configurations, dexterity, and stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…The experiment results along with detailed comparisons are presented in Figs. [17][18][19][20]. The trajectories of the end-effector positions (refer Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiment results along with detailed comparisons are presented in Figs. [17][18][19][20]. The trajectories of the end-effector positions (refer Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, from Eqs. (17) and (21), it is observed that the Lyapunov's candidate function is positive definite and its time derivative is negative definite in the entire state space. i.e.,…”
Section: Stability Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…have to be considered. The global stiffness and workspace of the parallel mechanisms vary with the configuration of the assembled parallel kinematic chains [1][2][3]. In fact, there is always a tradeoff between stiffness and workspace in the design of such mechanisms.…”
Section: Introductionmentioning
confidence: 99%